Economic-Mathematical Modelling of the Distribution of Investments in the Tourism and Hospitality - Korepanov, Oleksiy; Goncharenko, Yanislava; Mekhovich, Sergey; Dyshkantiuk, Oksana; Salamatina, Svitlana; Rusavska, Valentyna; Корепанов, Олексій Сергійович; Гончаренко, Яніслава; Мехович, Сергій; Дишкантюк, Оксана; Саламатіна, Світлана; Русавська, Валентина (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Among the world's leading concepts for the development of the tourism industry, a special place is occupied by the distribution of investments in tourism and hospitality. The theoretical aspects of the distribution of investments are analyzed in sufficient detail in scientific works, but there is a clear deficit of serious research on the mathematical modelling of the distribution of investments in the field of tourism and hospitality. The article presents the economic-mathematical model of the distribution of investments in tourism and hospitality. In this work, the investment strategy of activity of the travel agent is developed, depending on the received plan of realization of the developed tours.

Серед провідних світових концепцій розвитку туристичної галузі особливе місце займає розподіл інвестицій у туризм та гостинність. Теоретичні аспекти розподілу інвестицій достатньо детально проаналізовані в наукових працях, проте спостерігається явний дефіцит серйозних досліджень математичного моделювання розподілу інвестицій у сфері туризму та гостинності. У статті представлено економіко-математичну модель розподілу інвестицій у туризм та гостинність. У цій роботі розроблено інвестиційну стратегію діяльності туристичного агента залежно від отриманого плану реалізації розроблених турів.
Економіко-математичне моделювання розподілу інвестицій у сфері туризму та гостинності
Keywords: SOCIAL SCIENCES::Business and economics; SOCIAL SCIENCES::Statistics, computer and systems science::Statistics; economic-mathematical modelling; економіко-математичне моделювання; investments; інвестиції; hospitality; tourism; туризм